Canine Cutaneous Plasmacytosis: 21 Cases (2005–2015). (17th May 2017) - Boostrom, B.O.; Moore, A.S.; DeRegis, C.J.; Robat, C.; Freeman, K.; Thamm, D.H.
Abstract : Background: Cutaneous plasmacytosis (CP) is a syndrome of multiple cutaneous plasma cell tumors, in the absence of multiple myeloma. Although rare in both humans and dogs, treatment recommendations are usually extrapolated from multiple myeloma protocols. To date, no case series of CP have been described in the veterinary literature. Hypothesis/Objectives: To describe clinical presentation, determine treatment response rates and duration, and report overall survival of dogs with CP. Animals: Twenty‐one client‐owned dogs with CP. Methods: Medical records of 21 dogs with CP were reviewed. Diagnosis was based on histopathologic evaluation of at least 1 representative cutaneous or subcutaneous lesion in dogs with ≥3 lesions. Dogs with suspicion of multiple myeloma were excluded. Results: The most commonly affected breeds were the golden (5/21) and Labrador retriever (3/21). Fourteen of 21 dogs had >10 lesions, with some having >100. Lesions commonly were described as round, raised, pink‐to‐red, and variably alopecic or ulcerated. The most commonly used drug protocol was combined melphalan and prednisone, with an overall response rate (ORR) of 73.7% (14/19 dogs). Single‐agent lomustine was associated with a similar ORR of 71.4% (5/7 dogs). For all treatments combined, the median progression‐free interval after the first treatment was 153 days. The median survival time from the first treatment was 542 days. Conclusions and Clinical Importance: Alkylating agents were effective in inducing remission of CP; corticosteroids, melphalan, and lomustine were the most commonly used drugs. Survival times were similar to those reported in dogs with multiple myeloma treated with alkylating agents.